The Paradigm Shift From Patient to Health Consumer: 20 Years of Value Assessment in Health - Eline M van den Broek-Altenburg; Adam J Atherly (Journal of Medical Internet Research)
Health care is undergoing a “revolution,” where patients are becoming consumers and armed with apps, consumer review scores, and, in some countries, high out-of-pocket costs. Although economic analyses and health technology assessment (HTA) have come a long way in their evaluation of the clinical, economic, ethical, legal, and societal perspectives that may be impacted by new technologies and procedures, these approaches do not reflect underlying patient preferences that may be important in the assessment of “value” in the current value-based health care transition. The major challenges that come with the transformation to a value-based health care system lead to questions such as “How are economic analyses, often the basis for policy and reimbursement decisions, going to switch from a societal to an individual perspective?” and “How do we then assess (economic) value, considering individual preference heterogeneity, as well as varying heuristics and decision rules?” These challenges, related to including the individual perspective in cost-effectiveness analysis (CEA), have been widely debated. Cost-effectiveness measures treatments in terms of costs and quality-adjusted life-years (QALYs), where QALYs assume that a health state that is more desirable is more valuable, and therefore, value is equated with preference or desirability. QALYs have long been criticized for empirical and conceptual shortcomings. However, policy makers in many countries have used QALY measures to make health coverage decisions, although now, patients, and patient advocates, are questioning the valuation methodologies. This has led to the development of new approaches to valuing health, which are already starting to be used in the United States. This paper reviews 20-25 years of value assessment approaches in health and concludes with challenges and opportunities for value assessment methods in health in the years to come.